Demand & Supply Trends of Sparkling Metal - ,Ms. Anamika Hardia, Ms. Sheetal Dubey (International Journal of Scientific Research and Management (IJSRM), 2014)
As gold is an essential part of savings of a large number of investors, this has raised apprehensions whether any correction in gold prices will have destabilizing implications on the financial markets. In this backdrop, the paper makes an attempt to analyze the implications of the correction in gold prices on financial stability in India. The domestic Indian gold market is estimated to be more than US$ 20 billion and is expected to rise significantly in the coming years. The Indian gems and jewellery market is set to cross US$ 30.32 billion by 2014, on the back of improving lifestyle and availability of skilled labour, as per a report ‘Indian Gems And Jewellery Market – Future Prospects To 2011’, by RNCOS. The paper examine that due to the non availability of benchmark price, the gold prices in India vary very much from region to region. The festive and the wedding season in the country witnesses a heavy demand for gold. Despite the global economic recession, the gold consumption in the country during these times had not abetted. Based on empirical evidences, the paper also concludes that implication of moving average chart, price of gold having an uptrend and predicts the future trends of gold. This paper is another attempt to provide thoughts for some questions such as what are the expected returns form gold?, is demand supply of gold make any impact of gold price and its exponential growth?